Success and luck: good fortune and the myth of meritocracy - Frank, Robert H. (Princeton University Press, 2016)
"A New York Times economics columnist explores the findings in recent years by scientists who have discovered that chance plays a much larger role in important life situations than most people imagine, showing how a more accurate understanding of this discovery could lead to better, richer and fairer economies and societies,"--NoveList